The Analysis of Student Difficulties in Learning Mathematics in Class VIII Students at SMP Negeri 2 Hiliduho 2021/2022 - Andi Salfin Mendrofa; Natalia Mendrofa (PT FORMOSA CENDEKIA GLOBAL, 2023)
Learning difficulties are one of the external factors (from outside themselves) of students that have been identified as resulting in low student achievement in mathematics. These learning difficulties can be caused by many factors. This research aims to: (1) analyze students' difficulties in learning mathematics. (2) describe the student's mathematics learning difficulties in mathematics learning. This research was carried out at SMP Negeri 2 Hiliduho. This research is qualitative research with a descriptive approach. The results of data analysis show that: (1) in mathematics learning in Class VIII of SMP Negeri 2 Hiliduho, 69% of 23 students had difficulty learning mathematics. (2) Difficulty learning mathematics is caused by difficulty understanding concepts, difficulty finding the correct solution or formula to solve problems, students' lack of ability in operating numbers and students being unable to write answers correctly.